Evaluation of Nurse Workload in Patient Units - Astari, Dewanti Widya; Kartikaningsih, Kartikaningsih; Setiawan, Dede (GLOBAL HEALTH SCIENCE GROUP, 2024)
The inpatient room at a tertiary referral eye hospital includes eye surgery services and infection treatment for adult and pediatric patients. Nurse workload greatly influences the quality of service in the inpatient unit. However, data regarding the workload of nurses in inpatient units at tertiary referral eye hospitals is still limited. Objective: To determine the workload of nurses in the inpatient ward of a tertiary referral eye hospital. Method: This research is a quantitative descriptive study, which provides an overview of the workload of nurses in the inpatient ward of a tertiary referral eye hospital. The research was carried out from March to May 2023. The total sampling of research respondents was 25 nurses in inpatient treatment rooms for class 2 and 3 patients. Data collection used a workload questionnaire. Data analysis uses cross tabulation. The validity test was declared valid using the Pearson product moment correlation with results for the physical aspect of 0.396, the psychological aspect of 0.396 and the time aspect of 0.396 (0.396 > 0.312). Reliability test usingCronbach's alphawith a coefficient of more than 0.6, it is declared reliable, where the physical aspect is 0.945, the psychological aspect is 0.903 and the time aspect is 0.906. This research has received ethical approval number: LB.02.01/2.3/5440/2023. Results: research shows that the workload of nurses on the physical aspect is high, namely 76%, and the workload of nurses on the psychological aspect is high, namely 96%. Discussion: Several factors causing the high workload of nurses include the large number of patients entering the inpatient room, the bed management system which is not yet optimal, and the limited treatment space but continuous use of beds. Conclusion: The high workload of nurses has an impact on the quality of nursing services.